CONQUERING CONSUMERS' HEARTS: THE SECRET OF STORE ATMOSPHERE AND PRICES IN INCREASING PURCHASE INTEREST CASE STUDY: PD. SANLIA - Syaifuddin, Syaifuddin (Jurnal Ekonomi, 2023)
This research aims to investigate the influence of shop atmosphere and prices on consumer buying interest in PD. Sanlia. The research method used is quantitative using a questionnaire as a data collection tool. The research sample is PD consumers. Sanlia, with a total of 68 respondents. Data were analyzed using correlation analysis and multiple regression techniques. The research results show that both store atmosphere and price have a positive and significant influence on consumer purchasing interest individually and simultaneously. The results of the analysis show that the contribution of the influence of store atmosphere and price to consumer buying interest reached 84.7%, while the remaining 15.3% was influenced by other factors not examined in this research. The results of the significance test also show that the shop atmosphere and price simultaneously influence consumer buying interest at PD. Sanlia is significant. These findings emphasize the importance of paying attention to store atmosphere and prices in designing retail marketing and management strategies to increase consumer buying interest and achieve competitive advantage in the market.